State Capacity and Tolerance towards Tax Evasion: First Evidence from Romania - Călin Vâlsan; Elena Druică; Rodica Ianole-Călin (Administrative Sciences, 2020)
We investigate the level of tolerance towards tax non-compliance and the informal economy in Romania, using a sample of 250 respondents. This variable is determined by a complex set of latent variables that include, but is not limited to, state capacity, social and business norms, the perception of non-compliance, and the perception of distributive justice. We find that our respondents are intolerant towards tax evasion and the informal economy, but the level of intolerance is relatively mild. Using a partial least squares—path modeling approach, we also find that a weak state capacity and the perception of lack of distributive justice increases the level of tolerance. The perception of tax evasion stemming from media reports, and the respondents’ own self-enhancement bias, combine to push the level of tolerance lower.